LeTrungThanh Optical Biosensors Based on Multimode Interference and Microring Resonator Structures - Thanh, Le Trung (VNU Journal of Science: Natural Sciences and Technology, 2018)
We review our recent work on optical biosensors based on microring resonators (MRR) integrated with 4x4 multimode interference (MMI) couplers for multichannel and highly sensitive chemical and biological sensors. The proposed sensor structure has advantages of compactness, high sensitivity compared with the reported sensing structures. By using the transfer matrix method (TMM) and numerical simulations, the designs of the sensor based on silicon waveguides are optimized and demonstrated in detail.  We applied our structure to detect glucose and ethanol concentrations simultaneously. A high sensitivity of 9000 nm/RIU, detection limit of 2x10-4 for glucose sensing and sensitivity of 6000nm/RIU, detection limit of 1.3x10-5 for ethanol sensing are achieved. Keywords Biological sensors, chemical sensors, optical microring resonators, high sensitivity, multimode interference, transfer matrix method, beam propagation method (BPM), multichannel sensor References [1] Vittorio M.N. Passaro, Francesco Dell’Olio, Biagio Casamassima et al., "Guided-Wave Optical Biosensors," Sensors, vol. 7, pp. 508-536, 2007. [2] Caterina Ciminelli, Clarissa Martina Campanella, Francesco Dell’Olio et al., "Label-free optical resonant sensors for biochemical applications," Progress in Quantum Electronics, vol. 37, pp. 51-107, 2013. [3] Wen Wang (Editor), Advances in Chemical Sensors: InTech, 2012. [4] Lei Shi, Yonghao Xu, Wei Tan et al., "Simulation of Optical Microfiber Loop Resonators for Ambient Refractive Index Sensing," Sensors, vol. 7, pp. 689-696, 2007. [5] Huaxiang Yi, D. S. Citrin, and Zhiping Zhou, "Highly sensitive silicon microring sensor with sharp asymmetrical resonance," Optics Express, vol. 18, pp. 2967-2972, 2010. [6] Zhixuan Xia, Yao Chen, and Zhiping Zhou, "Dual Waveguide Coupled Microring Resonator Sensor Based on Intensity Detection," IEEE Journal of Quantum Electronics, vol. 44, pp. 100-107, 2008. [7] V. M. Passaro, F. Dell’Olio, and F. Leonardis, "Ammonia Optical Sensing by Microring Resonators," Sensors, vol. 7, pp. 2741-2749, 2007. [8] C. Lerma Arce, K. De Vos, T. Claes et al., "Silicon-on-insulator microring resonator sensor integrated on an optical fiber facet," IEEE Photonics Technology Letters, vol. 23, pp. 890 - 892, 2011. [9] Trung-Thanh Le, "Realization of a Multichannel Chemical and Biological Sensor Using 6x6 Multimode Interference Structures," International Journal of Information and Electronics Engineering, Singapore, vol. 2, pp. 240-244, 2011. [10] Trung-Thanh Le, "Microring resonator Based on 3x3 General Multimode Interference Structures Using Silicon Waveguides for Highly Sensitive Sensing and Optical Communication Applications," International Journal of Applied Science and Engineering, vol. 11, pp. 31-39, 2013. [11] K. De Vos, J. Girones, T. Claes et al., "Multiplexed Antibody Detection With an Array of Silicon-on-Insulator Microring Resonators," IEEE Photonics Journal, vol. 1, pp. 225 - 235, 2009. [12] Daoxin Dai, "Highly sensitive digital optical sensor based on cascaded high-Q ring-resonators," Optics Express, vol. 17, pp. 23817-23822, 2009. [13] Adrián Fernández Gavela, Daniel Grajales García, C. Jhonattan Ramirez et al., "Last Advances in Silicon-Based Optical Biosensors," Sensors, vol. 16, 2016. [14] Xiuyou Han, Yuchen Shao, Xiaonan Han et al., "Athermal optical waveguide microring biosensor with intensity interrogation," Optics Communications, vol. 356, pp. 41-48, 2015. [15] Yao Chen, Zhengyu Li, Huaxiang Yi et al., "Microring resonator for glucose sensing applications," Frontiers of Optoelectronics in China, vol. 2, pp. 304-307, 2009/09/01 2009. [16] Gun-Duk Kim, Geun-Sik Son, Hak-Soon Lee et al., "Integrated photonic glucose biosensor using a vertically coupled microring resonator in polymers," Optics Communications, vol. 281, pp. 4644-4647, 2008. [17] Carlos Errando-Herranz, Farizah Saharil, Albert Mola Romero et al., "Integration of microfluidics with grating coupled silicon photonic sensors by one-step combined photopatterning and molding of OSTE," Optics Express, vol. 21, pp. 21293-21298, 2013. [18] Trung-Thanh Le, "Two-channel highly sensitive sensors based on 4 × 4 multimode interference couplers," Photonic Sensors, vol. 7, pp. 357-364, 2017/12/01 2017. [19] Duy-Tien Le and Trung-Thanh Le, "Coupled Resonator Induced Transparency (CRIT) Based on Interference Effect in 4x4 MMI Coupler," International Journal of Computer Systems (IJCS), vol. 4, pp. 95-98, May 2017. [20] Trung-Thanh Le, "All-optical Karhunen–Loeve Transform Using Multimode Interference Structures on Silicon Nanowires," Journal of Optical Communications, vol. 32, pp. 217-220, 2011. [21] L.B. Soldano and E.C.M. Pennings, "Optical multi-mode interference devices based on self-imaging :principles and applications," IEEE Journal of Lightwave Technology, vol. 13, pp. 615-627, Apr 1995. [22] Trung-Thanh Le, Multimode Interference Structures for Photonic Signal Processing: LAP Lambert Academic Publishing, 2010. [23] J.M. Heaton and R.M. Jenkins, " General matrix theory of self-imaging in multimode interference(MMI) couplers," IEEE Photonics Technology Letters, vol. 11, pp. 212-214, Feb 1999 1999. [24] Trung-Thanh Le and Laurence Cahill, "Generation of two Fano resonances using 4x4 multimode interference structures on silicon waveguides," Optics Communications, vol. 301-302, pp. 100-105, 2013. [25] W. Green, R. Lee, and G. DeRose et al., "Hybrid InGaAsP-InP Mach-Zehnder Racetrack Resonator for Thermooptic Switching and Coupling Control," Optics Express, vol. 13, pp. 1651-1659, 2005. [26] Trung-Thanh Le and Laurence Cahill, "The Design of 4×4 Multimode Interference Coupler Based Microring Resonators on an SOI Platform," Journal of Telecommunications and Information Technology, Poland, pp. 98-102, 2009. [27] Duy-Tien Le, Manh-Cuong Nguyen, and Trung-Thanh Le, "Fast and slow light enhancement using cascaded microring resonators with the Sagnac reflector," Optik - International Journal for Light and Electron Optics, vol. 131, pp. 292–301, Feb. 2017. [28] Xiaoping Liang, Qizhi Zhang, and Huabei Jiang, "Quantitative reconstruction of refractive index distribution and imaging of glucose concentration by using diffusing light," Applied Optics, vol. 45, pp. 8360-8365, 2006/11/10 2006. [29] C. Ciminelli, F. Dell’Olio, D. Conteduca et al., "High performance SOI microring resonator for biochemical sensing," Optics & Laser Technology, vol. 59, pp. 60-67, 2014. [30] Trung-Thanh Le, "Two-channel highly sensitive sensors based on 4 × 4 multimode interference couplers," Photonic Sensors, pp. 1-8, DOI: 10.1007/s13320-017-0441-1, 2017. [31] O. A. Marsh, Y. Xiong, and W. N. Ye, "Slot Waveguide Ring-Assisted Mach–Zehnder Interferometer for Sensing Applications," IEEE Journal of Selected Topics in Quantum Electronics, vol. 23, pp. 440-443, 2017. [32] Juejun Hu, Xiaochen Sun, Anu Agarwal et al., "Design guidelines for optical resonator biochemical sensors," Journal of the Optical Society of America B, vol. 26, pp. 1032-1041, 2009/05/01 2009. [33] Y. Chen, Y. L. Ding, and Z. Y. Li, "Ethanol Sensor Based on Microring Resonator," Advanced Materials Research, vol. 655-657, pp. 669-672, 2013. [34] Sasikanth Manipatruni, Rajeev K. Dokania, Bradley Schmidt et al., "Wide temperature range operation of micrometer-scale silicon electro-optic modulators," Optics Letters, vol. 33, pp. 2185-2187, 2008. [35] Ming Han and Anbo Wang, "Temperature compensation of optical microresonators using a surface layer with negative thermo-optic coefficient," Optics Letters, vol. 32, pp. 1800-1802, 2007. [36] Kristinn B. Gylfason, Albert Mola Romero, and Hans Sohlström, "Reducing the temperature sensitivity of SOI waveguide-based biosensors," 2012, pp. 84310F-84310F-15. [37] Chun-Ta Wang, Cheng-Yu Wang, Jui-Hao Yu et al., "Highly sensitive optical temperature sensor based on a SiN micro-ring resonator with liquid crystal cladding," Optics Express, vol. 24, pp. 1002-1007, 2016. [38] Feng Qiu, Feng Yu, Andrew M. Spring et al., "Athermal silicon nitride ring resonator by photobleaching of Disperse Red 1-doped poly(methyl methacrylate) polymer," Optics Letters, vol. 37, pp. 4086-4088, 2012. [39] Biswajeet Guha, Bernardo B. C. Kyotoku, and Michal Lipson, "CMOS-compatible athermal silicon microring resonators," Optics Express, vol. 18, pp. 3487-3493, 2010. [40] Sahba Talebi Fard, Valentina Donzella, Shon A. Schmidt et al., "Performance of ultra-thin SOI-based resonators for sensing applications," Optics Express, vol. 22, pp. 14166-14179, 2014. [41] T. T. Bui and T. T. Le, "Glucose sensor based on 4x4 multimode interference coupler with microring resonators," in 2017 International Conference on Information and Communications (ICIC), 2017, pp. 224-228. [42] Chung-Yen Chao and L. Jay Guo, "Design and Optimization of Microring Resonators in Biochemical Sensing Applications," IEEE Journal of Lightwave Technology, vol. 24, pp. 1395-1402, 2006. [43] A. Yariv, "Universal relations for coupling of optical power between microresonators and dielectric waveguides," Electronics Letters, vol. 36, pp. 321–322, 2000. [44] Xiaoyan Zhou, Lin Zhang, and Wei Pang, "Performance and noise analysis of optical microresonator-based biochemical sensors using intensity detection," Optics Express, vol. 24, pp. 18197-18208, 2016/08/08 2016. [45] James H. Wade and Ryan C. Bailey, "Applications of Optical Microcavity Resonators in Analytical Chemistry," Annual Review of Analytical Chemistry, vol. 9, pp. 1-25, 2016.